Carcass characteristics and gut histomorphology of marshall broilers fed maxigrain supplemented diets (2013)
One hundred and forty four day-old Marshall Chicks were randomly assigned to six dietary treatments to assess the influence of a cocktail enzyme (maxigrain) on the carcass characteristics, visceral organ weights and gut morphology of Marshall Broilers. Completely randomised design was used for the study consisting six diets. Diet 1 was the control diet without enzyme, Diet 2; control diet with 0.1% Maxigrain inclusion, Diet 3; 5% energy reduction without enzynne, Diet 4; 5% energy reduction with 0.1% Maxigrain, Diet 5; 5% protein reduction without enzyme and Diet 6; 5% protein reduction with 0.1% Maxigrain. Diets were replicated four times with each replicate having 6 birds. Completely radomised design was used while the level of significance employed was p<0.05 Results indicates that carcass characteristics observed show that only drumsticks were significantly influenced by enzyme supplementation (p<0.05). Gizzard, (3.80g) spleen (0.20g) and abdominal fat (1.60g) were also significantly affected by Maxigrain supplementation. Values obtained for gut morphological assessment of the ileum and jejunum showed significant improvements (P<0.05) in the crypt depth, 130.30pm, 136.26pm villus height 111 1.80pm, 1426.90pm and villus to crypt ratio 12.82, 13.35 respectively, as a result of Maxigrain supplementation.